Shear failure mechanism and acoustic emission characteristics of jointed rock-like specimens - Ban, Yuxin; Qiang, Xie; Xiang, Fu; Rini Asnida Abdullah; Wang, Jingjing (Penerbit Universiti Kebangsaan Malaysia, 2021)
Evidence indicate that the stability of rock mass is highly associated with the shear behaviours of jointed surfaces under the effect of in situ stress conditions. Understanding the shear failure mechanism of jointed surface has great significance for tunneling and drilling engineering. Direct shear tests were conducted on jointed rock-like specimens to investigate the influence of joint roughness and normal stress on shear failure characteristics. In the present study, regular triangular sawtooth was produced to simulate different asperities. Based on the direct shear test, the specimens exhibited four types of failure modes: damage tend to occur on the sawtooth tips under low normal stress; whereas damage occurred on a large scale under high normal stress; a localized region of the sawtooth was worn when the dilation angle was small; meanwhile the sawtooth tips or base were cut off when the dilation angle was large. In addition, Acoustic Emission (AE) technology was adopted to synchronously monitor the development of cracks during testing. Further attempt has been carried out to simulate the crack initiation, propagation and coalescence using Particle Flow Code (PFC). The numerical model has successfully verified and explained the crack behaviors determined by the shear failure mechanism in the physical test. Additionally, the irregular profile was introduced in the PFC, it was found that the failure behavior in sawtooth profile has established a good conclusion to fully understand the failure mechanism in the irregular profile. This work can provide some reference for evaluating the behavior of underground engineering composed of jointed rock masses during the shearing.